Essential Thrombocytosis and Hepatocellular Carcinoma: A Mechanistic Challenge. (28th October 2021) - Mohammed, S
Abstract: Introduction/Objective: Thrombocytosis has been reported in 8.2% of patients with Hepatocellular carcinoma [HCC] and has been attributed to increased Thrombopoietin [TPO] production by the tumor. Methods/Case Report: We present a case of a 68-year-old male with a history of Hepatitis C and ethanol abuse presented with complaints of headache and chills. Imaging studies revealed a large mass in the liver [right lobe] suggesting an HCC of fibrolamellar type. His platelet count [PC] was 965 K/mcL. The serum AFP [Alpha feto protein] concentration was >51, 800 ng/ml. There was no evidence of metastatic disease and the patient was started on Capecitabine and radiation therapy targeting the liver mass. Lung metastasis became evident and Sorafenib was added. His PCs and AFP concentrations however continued decreasing to 306 K/mcL and 460.7 ng/ml respectively. His PC then increased to a peak of 1.32 million/mcL 10 months later. The molecular workup done at our reference lab was positive for CALR [Calreticulin] mutation. The patient was started on Hydroxyurea and his PC decreased to 323 K/mcL at the time of writing. His AFP has remained stable. This case illuminates the complicated relationship between HCC and thrombocytosis. The therapy directed against the HCC did decrease PC and AFP concentration in our case. The second wave of thrombocytosis led to the discovery of CALR mutation, and the patient was diagnosed with Essential Thrombocytosis [ET]. Treatment with Hydroxyurea again decreased the PC while AFP concentration was increased but stable. Thrombopoietin levels have remained stable for the patient after treatment with Hydroxyurea. Results (if a Case Study enter NA): NA Conclusion: Although the question of which mechanism(or possibly both) was at work in this case cannot be resolved definitely, two points are worth noting. The first is that- the assumption that the thrombocytosis was related to the HCC delayed testing for mutations associated with Essential Thrombocytosis. The second is that the TPO assay that may have yielded useful information in sorting out the alternatives was not ordered early enough before starting hydroxyurea.